2003
DOI: 10.1034/j.1478-3231.23.s.3.3.x
|View full text |Cite
|
Sign up to set email alerts
|

MARS therapy in critically ill patients with advanced malignancy: a clinical and technical report

Abstract: MARS was well-tolerated in critically ill patients with advanced and complicated cancer. Low-dose heparin was safe and did not compromise MARS circuit integrity. Although MARS had a significant de-uraemization effect, this appeared to be limited by the duration of MARS operation. Our data suggested that such a limit was reached earlier for total bilirubin. More data are needed to confirm the present findings and further delineate the saturation limit of MARS for different toxins that accumulate in ALF. This wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Non-specific PHLF studies. In the 17 non-specific PHLF studies, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] the treatment and outcomes of PHLF patients were pooled with other causes of liver failure making it impossible to extract specific information about the treatment of PHLF patients. In general, all studies reported a significant decrease of plasma bilirubin, creatinine and clinical improvement of pruritus and encephalopathy after MARS treatment.…”
Section: Mars In Phlfmentioning
confidence: 99%
“…Non-specific PHLF studies. In the 17 non-specific PHLF studies, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] the treatment and outcomes of PHLF patients were pooled with other causes of liver failure making it impossible to extract specific information about the treatment of PHLF patients. In general, all studies reported a significant decrease of plasma bilirubin, creatinine and clinical improvement of pruritus and encephalopathy after MARS treatment.…”
Section: Mars In Phlfmentioning
confidence: 99%
“…Data from the limited pediatric studies suggest that MARS therapy is not harmful to pediatric patients. There is only 1 case report of ELS use in a patient with severe VOD who did not survive, and thus it is difficult to make any evidencebased recommendations [115]. Moreover, this technology might not be available in most centers.…”
Section: Q10: What Are the Indications For Extracorporeal Liver Suppomentioning
confidence: 99%